Chlorine Dioxide Gas Retain Postharvest Quality and Shelf Life of Tomato during Modified Atmosphere Packaging Storage - Mohammad Zahirul Islam; Mahmuda Akter Mele; Jong Man Park; Il-Seop Kim; Ho-Min Kang (AGRIVITA, Journal of Agricultural Science, 2017)
While surface sterilization can minimize the postharvest loss of fruits and vegetables, it depends on concentration, treatment duration, storage condition, and crops. This study was conducted to investigate the consequences of chlorine dioxide (ClO2) gas on post-harvest quality and shelf life of tomato fruits during the modified atmosphere packaging storage. Tomato fruits of light red maturity stage were harvested at Gangwon province in the Republic of Korea. Fruits were dipped in fungal suspension and, afterward, some of them were sterilized with NaOCl, while others were sterilized with ClO2 gas. On the final storage day, the 5 ppm ClO2 gas 12 hours treated tomato fruits showed the least carbon dioxide and ethylene, and the utmost oxygen concentration. The least fresh weight loss, prolonged shelf life and the most suppressed fungal incidence were obtained by the 5 ppm ClO2 gas 12 hours treatment. As compared to other treatments, the 5 ppm ClO2 gas 12 hours treatment yielded higher firmness, titratable acidity and vitamin C, and lower soluble solids. Therefore, the 5 ppm ClO2 gas 12 hours treatment may be useful to prevent fungal incidence as well as to retain the postharvest quality and increase the shelf life of tomato fruits.